The Relationship Between Local Public Policies for Economic Development and Entrepreneurial Presence: The Italian Case. Issue 1 (January 2022) - De Matteis, Fabio; Bianchi, Piervito; Striani, Fabrizio; Preite, Daniela
The financial crisis has made the theme of economic development particularly significant. Analysis of this topic cannot ignore a key actor, that is, public administration. Here, we focus on all the Italian municipalities ( n = 7, 978), analyzing the relationship between local public policies (in terms of municipalities' governance and local governments' financial engagement) supporting urban economic development and local entrepreneurial presence (total number of active firms). Applying the general least square (GLS) method for over 4 years (2014–2017; n = 31, 912 observations), we find that the financial autonomy of cities and their financial efforts toward international programs, agriculture, agri-food and fisheries, tourism, culture, and economic development policies favor entrepreneurial presence. Our conclusion, contributing to public management and policy literature, also highlights some limits of the research and some related opportunities for further research on the subject.